Clinical-epidemiological characteristics and maternal risk factors related to fetal macrosomia - Gamarra-Luna, Sally Cheril (2024)
Objective: Determine the clinical-epidemiological characteristics and maternal risk factors related to fetal macrosomia in a Hospital of the Ministry of Health during the period from 2016 to 2022. Material and methods: The design was non-experimental, cross-sectional, comparative. There were 182 clinical records of newborns and their respective mothers. The information was collected through documentary analysis and electronic database review. The adjusted analysis was evaluated using logistic regression. Results: The results showed that the majority had less than or equal to 41 weeks of gestation (98.90%), female sex (59.89%) and vaginal delivery (77.47%). Among the maternal risk factors, it was found that they were nulliparous (55.49%), were overweight before pregnancy (46.15%), did not have adequate weight gain (50.55%), and did not present obesity at term (54.95%). It is concluded that the size of the newborn (aOR:1.27, p:0.001), the mother's height (aOR:1.10, p:0.001), adequate weight gain (aOR:1.62, p:0.045), obesity (ORa:2.26, p:0.012) were related to macrosomia. Conclusion: The size of the newborn, the mother, adequate weight gain and obesity are related to macrosomia.